Switching Behavior of Banks' Customers: Does It Exist? - Rizky Utami; Hermita Arif; Abdul Hamid Habbe; Faisal Abdullah (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2024)
This study aims to understand why the influence of switching behavior has a minimal effect on the improvement of market share in the Indonesian environment. This study examines Indonesian bank customers' switching behaviour using descriptive quantitative methods. Our random purposive sampling included persons working and using conventional and Islamic bank products and services. 128 respondents completed the online survey and met data analysis criteria. After general questions about respondents' profiles, the questionnaire examined switching behaviour. The data will be analysed to determine how respondents chose their bank and why they use Islamic or conventional banks. These data suggest that customers become more religiously committed and select Islamic banking. An important finding from this investigation was that customers were not fully switching to Islamic banks. Conventional bank services are used. The payroll system, notably for public employees and private company personnel, make it intriguing. Despite their strong religious beliefs, their customer agency contract with a conventional bank. This is the